Chlorinated Pesticide Residue Status in Tomato, Potato and Carrot - S. I. Khan, M.T.I. Chowdhury*, M. A. Razzaque and M. (Journal of Experimental Sciences, 2011)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> A study was carried out to identify the bioaccumulation and the ascertain level of chlorinated pesticide residues in some vegetables collected from market baskets of New market, Dhaka, Bangladesh namely potato, tomato and carrot. The samples were randomly collected from different shops and analyzed by capillary column of Gas Chromatograph Mass Spectrometry (GCMS) with Electron Impact Ionization (EI) method for the detection of chlorinated pesticide. The results of the study revealed that collected samples of potato, tomato, red amaranth and spinach were contaminated with some chlorinated substances. But Indian spinach and carrot were free of contamination with organochlorine pesticide.